Komparasi Kebijakan Politik, Ekonomi, dan Keagamaan Antara Akbar Agung dan Sultan Agung - Yuana Tri Utomo (Mukaddimah: Jurnal Studi Islam, 2022)
Writing about the greatness of the history of Islamic civilization has been presented by many intellectuals from various backgrounds. However, many pearls of civilization are still buried inviting the next researchers to dig it back. The study of the history of Islamic civilization requires precision because of different perspectives due to various interpretations of historical facts. In general, the history of Islam starts from the time of Prophet Muhammad SAW (571 M) tothe present modern era. This paper describes the figure of two Muslim rulers in their respective periods and territories, namely Akbar Agung (1542-1605 M) in Hindia and Sultan Agung (1593-1645 M) in Nusantara.This paper uses a phenomenological descriptive approach by comparing the three variables: the political side, the economic sideand the religious attitudes. Intake of data through literature studies from various libraries exist in several libraries of Yogyakarta, from collection books and from interviews of cultural figures. Then the data is analyzed with three step triangulation: reduction, display and conclution drawing.The results reveal that the phenomenon of Akbar Agung in India and Sultan Agung in the archipelago in the field of politics, economic and religious still felt today. In the very prominent political field of Akbar Agung is an Indian territory that stretches with interfaith unity, while Sultan Agung becomes the National Hero of Indonesia for his services against the Dutch colonization. In the most prominent economic field for Akbar Agung is the prohibition of taxes for nonMuslims and for Sultan Agung is the VOC>s debt to oppose the VOC. In the most prominent religious field for the Great Akbar is the teachings of the Divine and for Sultan Agung is the unifying of the Javanese calendar and Islam. Keywords: Islamic Civilization, Political, Economic and Religion Comparative.